Be Patient, Little Chick - Jensen, Patricia; Erost; ClGement, Claude, 1946- (Pleasantville, N.Y. : Reader's Digest Kids, 1993)
Impatient to grow up, Little Chick learns to appreciate his mother's advice and protection when confronted by an angry rooster. Includes facts about hens and chicks.
aAdaptation of: Petit poussin pressGe / Claude ClGement.
Keywords: Chickens -- Fiction; Animals -- Infancy; Size -- Fiction; Patience -- Fiction